2022
DOI: 10.3390/sports10010007
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Body Composition and Strength after 12 Weeks of High-Intensity Functional Training with Two Different Loads in Physically Active Men and Women: A Randomized Controlled Study

Abstract: This study examined the effects of two different resistance loads during high-intensity Functional Training (HIFT) on body composition and maximal strength. Thirty-one healthy young individuals were randomly assigned into three groups: moderate load (ML: 70% 1-RM), low load-(LL: 30% 1-RM), and control (CON). Each experimental group performed HIFT three times per week for 12 weeks with a similar total volume load. Body fat decreased equally in both experimental groups after 6 weeks of training (p < 0.001), b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…The body composition measures showed significant differences between pre- and post-tour values in BW, ∑ 3 Skinfolds, SMM, and BFP; although the ES of these changes was only “moderate”, this does not coincide with another five-week study of unsupervised training in university tennis players, where no significant decreases were found in the body composition [ 13 ]. In this aspect, the information seems to be contradictory, since there are studies in other population groups and sports that do not indicate significant differences in fat-free mass or body fat percentage product of similar periods of training [ 40 , 41 ], and, on the contrary, others indicate significant changes, both in BFP and SMM [ 39 , 42 , 43 ]. However, the influence of training and competition on body composition modifications, both in SMM and BFP have been reported for different sports, highlighting that these modifications are influenced by sports and physical activity in young boys [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The body composition measures showed significant differences between pre- and post-tour values in BW, ∑ 3 Skinfolds, SMM, and BFP; although the ES of these changes was only “moderate”, this does not coincide with another five-week study of unsupervised training in university tennis players, where no significant decreases were found in the body composition [ 13 ]. In this aspect, the information seems to be contradictory, since there are studies in other population groups and sports that do not indicate significant differences in fat-free mass or body fat percentage product of similar periods of training [ 40 , 41 ], and, on the contrary, others indicate significant changes, both in BFP and SMM [ 39 , 42 , 43 ]. However, the influence of training and competition on body composition modifications, both in SMM and BFP have been reported for different sports, highlighting that these modifications are influenced by sports and physical activity in young boys [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…These values partially coincide with those of Luna-Villouta et al [ 1 ], who detected the loss of SMM, but unlike this study, they reported a decrease in BFP and ∑3 skinfolds. In this aspect, there are several studies reporting different results [ 42 , 43 , 44 , 45 ], which shows the complexity of these aspects in young athletes due to the influence of maturation, growth, nutrition, and training level [ 46 , 47 ]. Thus, it has been detected that high levels of fat mass affect physical performance in young athletes [ 46 , 48 , 49 ], for example, in the 5 m sprint of young tennis players [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…HIFT programs can reduce body fat [1,8]; therefore, such programs are promoted as an effective approach in terms of weight and fat loss in overweight individuals, as a recent systematic review and network metanalysis showed [20]. In another recent study, only HIFT programs using low-load exercises were able to reduce body fat, as opposed to a HIFT program with moderate-load exercises, which did not [10]. However, the effectiveness of such programs in increasing muscle mass is still debatable.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some recent studies examined the effects of various HIFT programs on physical fitness and body composition parameters. For example, 12 weeks of HIFT using low or medium load was equally effective in improving lean body mass and maximal strength, although only the low-load group exhibited reductions in body fat [10]. In addition, participation in CrossFit for six months improved physical fitness parameters, including muscle strength and endurance [5].…”
Section: Introductionmentioning
confidence: 99%